Cell Signaling of Caenorhabditis elegans in Response to Enterotoxigenic Escherichia coli Infection and Lactobacillus zeae Protection - Zhou, Mengzhou; Liu, Xiaozhen; Yu, Hai; Yin, Xianhua; Nie, Shao-Ping; Xie, Ming-Yong; Chen, Wei; Gong, Joshua (Frontiers in Immunology, 2018)
Enterotoxigenic Escherichia coli (ETEC) infection causes the death of Caenorhabditis elegans, which can be prevented by certain Lactobacillus isolates. The host response of C. elegans to ETEC infection and its regulation by the isolates are, however, largely unclear. This study has revealed that, in agreement with the results of life-span assays, the expression of the genes encoding p38 mitogen-activated protein kinase (MAPK) pathway (nsy-1, sek-1, pmk-1), insulin/insulin-like growth factor (DAF/IGF) pathway (daf-16), or antimicrobial peptides (lys-7, spp-1, abf-3) and other defensing molecules (abf-2, clec-85) was upregulated significantly when the wild-type nematode (N2) was subjected to ETEC infection. This upregulation was further enhanced by the pretreatment with Lactobacillus zeae LB1, but not with L. casei CL11. Mutants defective in the cell signaling of C. elegans were either more susceptible (defective in NSY-1, SEK-1, PMK-1, or DAF16) or more resistant (defective in AGE-1, DBL-1, SKN-1, or SOD-3) to ETEC infection compared with the wild-type. Mutants defective in antimicrobial peptides (LYS-7, SPP1, or ABF-3) were also more susceptible. In addition, mutants that are defective in NSY-1, SEK-1, PMK-1, DAF16, ABF-3, LYS-7, or SPP1 showed no response to the protection from L. zeae LB1. The expression of the genes encoding antimicrobial peptides (lys-7, spp-1, abf-3) and other defensing molecules (abf-2, clec-60, clec-85) were almost all upregulated in AGE-1- or DBL-1-defective mutant compared with the wild-type, which was further enhanced by the pretreatment of L. zeae LB1. The expression of these genes was, however, mostly downregulated in NSY-1- or DAF-16-defective mutant. These results suggest that L. zeae LB1 regulates C. elegans signaling through the p38 MAPK and DAF/IGF pathways to control the production of antimicrobial peptides and defensing molecules to combat ETEC infection.